U-TXM: a novel biomarker for early detection of diabetic kidney disease - Jin, Yujie; Xu, Jiahao; Ma, Yan; Ni, Chunchen; Yao, Yan; Shang, Shujuan; Wang, Mengru; Xing, Chunyan; Dong, Song; Xiong, Chaoqun; Xie, Kang; Zhang, Ruixi; et al. (Frontiers in Endocrinology, 2025)
Background and aimsDiabetic kidney disease (DKD) is the leading cause of end-stage renal disease. This study aimed to investigate the potential of urinary 11-dehydrothromboxane B2 (U-TXM) as a biomarker for the early detection of DKD.Materials and methodsA total of 690 patients were enrolled, including 422 with diabetes mellitus (DM) and 268 with DKD. Patients with type 1, type 2, and other specific forms of diabetes were consecutively recruited from the Department of Endocrinology, Yijishan Hospital of Wannan Medical College (April–September 2024). U-TXM levels were measured and their clinical relevance to DKD was evaluated using correlation analysis, logistic regression, and receiver operating characteristic (ROC) curve analysis.ResultsUrinary U-TXM levels were significantly higher in patients with DKD than in those with DM (median: 1158.05 vs. 960.44 pg/mg Cr; P<0.001). When stratified by renal function, U-TXM remained elevated in DKD regardless of serum creatinine (Cr) level (>70 or ≤70 μmol/L, both P<0.001). Multivariate analysis confirmed the existence of an independent association between DKD and U-TXM (OR=1.778, P=0.001), serum Cr (odds ratio [OR]=2.861, P<0.001), and systolic blood pressure (SBP, OR=1.032, P=0.001). U-TXM correlated positively with the urine albumin-to-Cr ratio (r=0.225, P<0.001), but only weakly with Cr and blood urea nitrogen. ROC analysis showed limited diagnostic value for U-TXM alone (area under the curve [AUC]=0.625), which improved substantially when combined with serum Cr and SBP (AUC=0.803).ConclusionU-TXM shows potential as a biomarker for DKD, particularly in patients at early disease stages. Validation through longitudinal, multicenter, and comparative studies is required to confirm its clinical utility.